EFFECTS OF PULMONARY REHABILITATION IN ACTIVE SMOKERS (CIPEEX, 2025)
Introduction: According to the National Cancer Institute, smoking is considered a chronic and epidemic disease resulting from nicotine dependence present in tobacco-derived products. Objective: To analyze, through a literature review, the effects of pulmonary rehabilitation on respiratory function and quality of life in smokers, highlighting its therapeutic interventions, clinical benefits, and the encouragement of adopting healthy lifestyle habits. Method: This is an integrative literature review. The search was conducted in the Scopus, PubMed, SciELO, and Web of Science databases. Articles addressing Pulmonary Rehabilitation and Respiratory Function in Smokers were included, while exclusion criteria comprised duplicate articles and studies involving non-adult populations. Results: Studies show that pulmonary rehabilitation promotes improvements in both functional capacity and maximal performance in exercise tests of patients with different chronic pulmonary symptoms. Considering that smoking contributes to most COPD cases and plays a role in disease progression, pulmonary rehabilitation programs provide a unique opportunity to address smoking cessation. Conclusion: The results of this study highlight the positive effects of pulmonary rehabilitation in active smokers. These programs improve respiratory function, functional capacity, quality of life, and contribute to reducing cigarette consumption, favoring smoking cessation. Therefore, pulmonary rehabilitation proves to be an effective intervention to promote clinical and behavioral gains.
Keywords: Smoking; Respiratory Function; Pulmonary rehabilitation; Physical Therapy